Transformations of the labor markets in Turkey and Germany - (:unkn) unknown (Peter Lang AG, 2015)
Since the implementation of neo-liberal economy policies significant changes have been taking place in the countries' labor markets. A transformation is observed from a labor market structure, which has more or less realized its goal of full employment, towards flexible labor markets. The scope of this study is to analyze the way the labor markets of Germany and Turkey are affected by this process. The developments in the fields of unemployment, informal economy, social gender, wages and syndication depending on the flexibilization policies are evaluated. Another intention is to reveal the qualities of the active and passive labor policies implemented by the two countries. In this study, the basic features of the labor markets of Germany, which receives one of the biggest shares of worldwide economies and is one of the leading countries with respect to technology production, are compared with those of Turkey, a country which tries to grow up but realizes this in dependence of hot money flow and debts, without being based on stable foundations. Moreover, liberal theses are tested within the study and the way Germany has established welfare from the perspective of the labor is also studied. The striking features of the flexibilization process of labor markets in Germany and Turkey will be compared as well. © Peter Lang GmbH.
Keywords: Flexibilization; labor markets; neo-liberal policies; passive and active labor market policies.